Left to Envy (An Adele Sharp Mystery-Book Six) - Blake, Pierce (Lukeman Literary, 2020)
"When you think that life cannot get better, Blake Pierce comes up with another masterpiece of thriller and mystery! This book is full of twists and the end brings a surprising revelation. I strongly recommend this book to the permanent library of any reader that enjoys a very well written thriller." --Books and Movie Reviews, Roberto Mattos (re Almost Gone) LEFT TO ENVY is book #6 in a new FBI thriller series by USA Today bestselling author Blake Pierce, whose #1 bestseller Once Gone (Book #1) (a free download) has received over 1,000 five star reviews. In the Sistine Chapel, the first tourists of the day look up-and are horrified to find a dead body affixed by ropes to the ceiling. More victims soon appear, strung up in similarly dramatic fashion on other major attractions throughout Europe. Who is killing them? Why? Who will be next? And is FBI Special Agent Adele Sharp-triple agent of the U.S., France and Germany-brilliant enough to enter the serial killer's mind and stop him before it's too late? An action-packed mystery series of international intrigue and riveting suspense, LEFT TO ENVY will have you turning pages late into the night. Book #7 in the series-LEFT TO LAPSE-is now also available.
Keywords: Krimi, detektivky